Holistic approach supporting mental wellbeing of people in enforced quarantine in South Australia during the COVID‐19 pandemic. (7th June 2021) - D'Onise, Katina; Meena, Sonali; Venugopal, Kamalesh; Currie, Marc; Kirkpatrick, Emily; Hurley, Jenny; Nolan, Rebecca; Brayley, John; Atherton, Bryan; Spurrier, Nicola
Abstract: Objectives : To report the experience of quarantine for international arrivals to South Australia requiring quarantine in a medi‐hotel setting during the COVID‐19 pandemic and to describe the range of evidence‐based support services to mitigate the mental health impacts of quarantine. Methods : A range of services targeted at physical and mental wellbeing were provided. Data from 533 adult respondents out of 721 passengers were included. The Kessler 10 was used to measure psychological distress at two time points. Results : About 7.1% of respondents reported psychological distress at time one, reduced to 2.4% at time two. There was no significant difference in psychological distress by gender at either time point. The mean K10 score at time one was 13.6 (standard deviation=5.2) and the mean score at time two was 11.5 (standard deviation=3.1), with a significant reduction in mean scores ( p <0.001) between the two time points. Conclusions : The level of psychological stress in repatriated Australians was low at arrival and improved further at the time of release from quarantine. Implications for public health : A collaborative multi‐sector approach to provide support services for individuals in quarantine can mitigate risks to mental wellbeing.